The Effect of Supervision and Work Discipline on The Work Effectiveness of Members in The Divpropam of The Police Republic of Indonesia - Restu Nurlaela; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti Publisher, 2026)
The objectives of this study are as follows: To determine the effect of supervision on work effectiveness, to determine the effect of work discipline on work effectiveness and to determine the effect of supervision and work discipline. together on the effectiveness of member work, the calculated t value for variable X1 (Supervision) is 8.004, while the t table value for n = 68 is 1.998. So 8.004 > 1.998. it can be concluded that Supervision (X1) does have an influence on work effectiveness, the calculated t value for variable X2 (Discipline) is 8,811, so 8,811 > 1.998, because tcount > ttable, then H0 is rejected and Ha is accepted and it can be concluded that Discipline (X2) does have an influence on Work Effectiveness. The calculated F value for both variables, namely Supervision (X1) and Discipline (X2), obtained an F count value of 135,531. While the Ftable (a0.05) n = 68 is 2.75. so Fcount > Ftable or 135,531 > 2.75. Thus H0 is rejected and Ha is accepted. It can be concluded that between Supervision and Discipline simultaneously does have an effect on work effectiveness